UJI DAYA ANTIBAKTERI DAN IDENTIFIKASI ISOLAT SENYAWA KATEKIN DARI DAUN TEH (Camellia sinensisL. var Assamica) - Christina Astutiningsih; Wahyuning Setyani; Himawan Hindratna (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: Antibacterial is a substance that can interfere with the growth and metabolism of bacteria, sothat these substances can inhibit growth or even kill bacteria. This research aimed to utilize naturalmaterials as a natural antibacterial. This study investigated the ability of isolates catechins of tea leaves toinhibit Staphylococcus aureus and spectral identification of these catechins. Catechin compounds wasextracted by water, and then fractionated with CHCl3 and ethyl acetate. Ethyl acetate phase wasconcentrated fractionation results using a rotary evaporator for further separation using thin layerchromatography with various mobile. The results of the study showed that the concentration of isolates ofdemonstrated to be effective as antibacterial, with MIC 12.5%. UV spectrum measurement showed that theisolates had a maximum absorption at a wavelength of 279 nm while the FTIR spectrophotometer showedthat isolates catechin-containing functional groups C = C aromatic absorption 1500-1600 nm^-1 and OHgroups, a broad band between 2000 and 3600 nm^-1.Key words: isolates catechins, Staphylococcus aureus, tea leaves, antibacterial